THE MULTILEVEL INTERPLAY OF ETHICAL LEADERSHIP WITH LEADER IDENTIFICATION AND AUTONOMOUS MOTIVATION TO CULTIVATE GREEN BEHAVIOUR PRACTICES - Mah Noor Shehzadi; Aqsa Shabbir; Numair Nisar (International Journal of Contemporary Issues in Social Sciences, 2024)
Implementing environmental regulations in Pakistan remains an ideological thought with little or no enforcement. In this context, an organization’s sincerity towards corporate social responsibility initiatives is proven when it operates responsibly without regulatory pressures. Aimed at advancing the discourse on social identity and self-determination theories, this paper examines the influencing mechanism of multilevel Ethical leadership on employees’ green behaviour practices from a vertical perspective through leader identification and autonomous motivation for the environment. The sample included 357 employees working in 97 teams from pharmaceutical, cement manufacturing, and textile sector companies. Multi-source data were collected in two phases and analyzed with multilevel structural equation modeling through MPlus 8.3 software. The results support the hypothesized direct and mediating mechanisms of Ethical leadership in shaping employees’ green behaviour practices. Theoretical and managerial implications, limitations, and future research suggestions are discussed.